Expanding peace journalism comparative and critical approaches - Lynch, Jake; Shaw, Ibrahim Seaga; Hackett, Robert A. (Sydney University Press, 2011)
This major new text explores and interrogates peace journalism as a significant challenge to this hegemonic discourse, which has been advocated and elaborated over the recent years in journalism, media development and academic spheres. J Lynch, University of Sydney.